Dillenia suffruticosa dichloromethane root extract induced apoptosis towards MDA-MB-231 triple negative breast cancer cells - Foo, J. B.; Saiful Yazan, Latifah; Tor, Yin Sim; Wibowo, Agustono; Ismail , N.; Nurdin, Armania; Cheah, Yoke Kqueen; Abdullah, Rasedee (Elsevier, 2016)
Ethnopharmacological Relevance: Dillenia suffruticosa is traditionally used for treatment of cancerous growth including breast cancer in Malaysia.